2017
DOI: 10.17503/agrivita.v39i3.1076
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Phenolic and Flavonoid Contents, Antioxidant Activities and GC-MS Analysis of Clinacanthus nutans (Acanthaceae) in Different Locations

Abstract: Clinacanthus nutans is an essential medicinal plant that had been used in various local remedies to treat many illnesses. A study had been conducted to determine the phenolic, flavonoid, antioxidant activities and phytochemical compounds of C. nutans in different locations. C. nutans were harvested from eight locations and the leaves were extracted with 80 % methanol by maceration process. Then, the phytochemical screening using Gas Chromatography-Mass Spectrometry (GC-MS), 2,2 diphenyl-2-picrylhydrazyl hydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…However, Alam et al [27] reported that the crude methanol extract of C. nutans leaves had the lowest scavenging activity. These differences in results likely occurred because the plants are largely influenced by environmental conditions, such as temperature, rainfall, water variability, humidity, variations in soil pH, nutrient contents, and exposure to soil microorganisms [28]. Moreover, environmental factors interact with the genetics of the plants, which lead to genetic variations [29] that affect the phytochemical contents.…”
Section: Antioxidant Capacitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Alam et al [27] reported that the crude methanol extract of C. nutans leaves had the lowest scavenging activity. These differences in results likely occurred because the plants are largely influenced by environmental conditions, such as temperature, rainfall, water variability, humidity, variations in soil pH, nutrient contents, and exposure to soil microorganisms [28]. Moreover, environmental factors interact with the genetics of the plants, which lead to genetic variations [29] that affect the phytochemical contents.…”
Section: Antioxidant Capacitiesmentioning
confidence: 99%
“…The TPC of C. nutans crude and fraction extracts was measured following Ismail et al [28], with slight modification. First, 1000 µg of each extract were diluted using 50% methanol to obtain 1000 µg/mL of sample concentration and then 1 mL of 100% Folin-Ciocalteu reagent was mixed with 9 mL of distilled water.…”
Section: Tpcmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants contribute many essential nutrients, vitamins and chemical compounds. Therefore, plants play an important role in the development of new drugs for the treatment and prevention of diseases [4][5][6][7] . Physalis minima is a member of the Solanaceae family and is known as letup-letup in Malaysia.…”
Section: Introductionmentioning
confidence: 99%